Alterations in the rumen bacterial communities and metabolites of finishing bulls fed high-concentrate diets supplemented with active dry yeast and yeast culture - Gao, Kai; Geng, Chunyin (Frontiers in Microbiology, 2022)
This study investigated the effects of active dry yeast (ADY) and yeast culture (YC) supplementation on rumen bacteria and metabolites in finishing bulls fed high-concentrate diets using the full-length 16S rDNA gene sequencing and liquid chromatography-mass spectrometry. Supplementation with ADY improved the alpha diversity and relative abundance of rumen bacteria, while YC only affected relative abundance of rumen bacteria at the genus level. Sixty-three differential metabolites were identified in rumen fluid after ADY supplementation, and 17 after YC. PICRUSt2 functional prediction showed that ADY supplementation improved the capacity of amino acid metabolism, lipid metabolism, carbohydrate metabolism, metabolism of terpenoids and polyketides, and energy metabolism in rumen bacteria (all P < 0.05). Correlation analysis showed that the rumen differential metabolites following ADY supplementation were mainly related to Oligosphaera, Verruc, Mycoplasma, and Anaeroplasma. Supplementation with ADY was more effective than YC in remodeling the rumen bacterial flora structure and metabolite composition under high-concentrate diets.